Bacterial wilt suppression and yield enhancement in Bhoot jolokia, Capsicum chinense using microbial consortial antagonists - Bora, Lohit C; Kataki, Lohit; Talukdar, Kuldeep; Kipgen, T L; Sharma, P; Khan, P; Dutta, J (Indian Journal of Plant Protection, 2020)
Saprophytic antagonists, Trichoderma viride, T. parareesei, Metarhizium anisopliae, Verticillium lecanii, Bacillus thuringiensis and their consortial formulations were evaluated for the management of bacterial wilt disease of Bhoot jolokia (Capsicum chinense) caused by Ralstonia solanacearum. The antagonists could inhibit the growth of the test pathogen in vitro. The highest inhibition (90.3%) against R. solanacearum was recorded by combination of B. thuringiensis + T. parareesei + M. anisopliae + T. viride followed by combination of B. thuringiensis (60.0%). Quantitative aspect of population dynamics of the selected antagonists in talc based substrate (containing carboxy methyl cellulose, mannitol and chitin as standard additives) was compared to evaluate their shelf-life of storage at room temperature. A steady population count was recorded in antagonist based bio-formulations up to 180 days of storage at room temperature. However, highest population recovery was found in the talc based formulation of B. thuringiensis followed by T. viride at 180 days of storage. The best combination of bio-formulations were selected for field evaluation and applied in planta as combination of seed treatment, soil application and sprays at 30 days after transplanting. Maximum disease reduction (83.9%) was recorded in talc based consortium formulation containing B. thuringiensis + T. parareesei + M. anisopliae + T. viride.